Motivasi Pembelotan Broker Politik: Studi Kasus Projo Ganjar dalam Pilpres 2024 - Fadillah, Mochamad Rayhan; Perdana, Aditya (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
This article explores the reasons why brokers shift from candidates with high winning prospects and substantial resources to candidates with lower winning prospects and fewer resources ahead of the 2024 elections. Building on Aspinall's study, the research aims to analyze the motivations behind the formation of Projo Ganjar by several Projo cadres who did not follow Jokowi's directive to support Prabowo Subianto, despite Prabowo having high winning prospects and substantial resources. A qualitative method was employed through in-depth interviews with key informants and literature review. The findings indicate that broker defections are driven by non-material factors such as incompatibility with the patron, changes in patron behavior, and alignment with other candidates. This study emphasizes that the relationship between brokers and candidates is not solely based on material benefits but is also influenced by non-material factors.